Identity in Britain: A cradle-to-grave atlas - Thomas, B; Dorling, D (Policy Press, 2007)
Sixty million people live in Britain. Imagine sixty million. Imagine a map of sixty million. What would that map look like and what story would it tell us about identity in Britain today? Bethan Thomas and Danny Dorling have brought together this outstanding atlas to provide us with a unique visual picture of identity and geography combined. "Identity in Britain" explores our changing identities as we progress from infancy to old age and tells the story of the myriad geographies of life in Britain.